The Role of Movies and Music on the English Proficiency of Freshmen and Sophomores at Universitas Advent Indonesia - Yenni Christina; Wijaya, Arzeti Celina (11th International Scholars Conference, 2024)
This study investigated the impact of integrating movies and music into English lessons on the language proficiency of freshmen and sophomores majoring in English at Universitas Advent Indonesia. The primary objective was to explore the potential of multimedia resources, specifically English-language movies and music, to enhance vocabulary acquisition, listening comprehension, and overall language proficiency. Employing a quantitative research approach with a survey method, the study gathered data through surveys and analyzed the effects of these multimedia tools on students’ language development. The findings revealed that students exposed to movies and music in English showed significant improvements in vocabulary retention, listening skills, and English fluency. Moreover, the engaging nature of these multimedia resources created a more stimulating and motivating learning environment compared to traditional methods. The study underscores the value of incorporating movies and music into language instruction as a means to improve learning outcomes and foster a more dynamic and effective educational experience in higher education.